Applications of energy absorption strategies in industry - Ba Zedong David Herbert (2013)
The purpose of this study is to review the current practices for energy absorption devices in the industry. The industries that were reviewed were maritime, sports and coastal engineering. The information obtained on existing energy absorption devices was then classified based on the main characteristic that enabled it to function. With this categorization, information on the current technologies in the commercial sector can be better understood and improved further if required. For the secondary purpose, an attempt was made to replicate and analyse a particular study done in the past which investigated the influence of impact objects on force absorption of mouth guard material. The present study was conducted through the use finite-element analysis software, ABAQUS. The parameters and variables of the experimental setup were made to be as identical as possible with the available information from the past study. The results obtained were different in magnitude as the past study due to differences in parameters that were not available. However, the overall trend of the results which included peak transmitted force, absorption ability of mouth guard was similar to a large extent. These results showed that testing of sports energy absorption devices through the use of finite-element modelling is accurate and similar to that of the actual environment. Therefore, future investigations could be emulated through finite-element analysis software. Conditions and specific parameters could then be set and carried out with ease as compared to actual physical tests.